Stable Heterometallic Cluster‐Based Organic Framework Catalysts for Artificial Photosynthesis - Dong, Long‐Zhang; Zhang, Lei; Liu, Jiang; Huang, Qing; Lu, Meng; Ji, Wen‐Xin; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2020)
A series of stable heterometallic Fe2M cluster‐based MOFs (NNU‐31‐M, M=Co, Ni, Zn) photocatalysts are presented. They can achieve the overall conversion of CO2 and H2O into HCOOH and O2 without the assistance of additional sacrificial agent and photosensitizer. The heterometallic cluster units and photosensitive ligands excited by visible light generate separated electrons and holes. Then, low‐valent metal M accepts electrons to reduce CO2, and high‐valent Fe uses holes to oxidize H2O. This is the first MOF photocatalyst system to finish artificial photosynthetic full reaction. It is noted that NNU‐31‐Zn exhibits the highest HCOOH yield of 26.3 μmol g−1 h−1 (selectivity of ca. 100 %). Furthermore, the DFT calculations based on crystal structures demonstrate the photocatalytic reaction mechanism. This work proposes a new strategy for how to design crystalline photocatalyst to realize artificial photosynthetic overall reaction. A series of stable heterometallic Fe2M cluster‐based MOFs achieve the overall conversion of CO2 and H2O into HCOOH and O2 without the assistance of additional sacrificial agent and photosensitizer. A strategy is proposed to design crystalline photocatalysts to realize the overall artificial photosynthetic reaction.